A 2007 Social Accounting Matrix for Uganda - Thurlow, James (International Food Policy Research Institute, 2012)
The Ugandan Social Accounting Matrix (SAM) is based on newly estimated supply-use tables, national accounts, government budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Uganda' s economy. It separates 37 activities and commodities; 5 types of factors of production; and 5 representative household groups. Labor and household information is drawn from a nationally representative household survey. The SAM also identifies government, investment and foreign accounts. It provides an ideal tool for economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling. The 2007 SAM for Uganda was developed by the Development Strategy and Governance Division (DSGD) at IFPRI, in partnership with the World Institute for Development Economics Research of the United Nations University in Helsinki, Finland. It was partly funded by USAID as part of their support to DSGD's Uganda Country Strategy Support Program (USSP). A 2004/05 version of the Malawi SAM was first used to evaluate options for agricultural growth and poverty reduction. The results of the Uganda case study is published in Diao, Xinshen; Thurlow, James; Benin, Samuel; and Fan, Shenggen. 2012. Strategies and priorities for African agriculture: Economywide perspectives from country studies. Washington, DC: International Food Policy Research Institute (IFPRI). http://ebrary.ifpri.org/cdm/ref/collection/p15738coll2/id/127049